Caklempong in Java Applet / Muhammad Nazli Shahruddin - Shahruddin, Muhammad Nazli (1997)
Main objective behind this project is the development of the Caklempong In Java Applet which run in the Netscape to give information to the people. When people go to the homepage, they will get the information about Caklempong and also play with the instruments. When the application is in Netscape, therefore it would be listened worldwide within the Internet networks. The Malaysian traditional Music can be access from any part of the world.